RESIDUAL CONTENTS OF SELECTED HEAVY METALS IN COMMERCIAL CANNED FISH IN EGYPT: DIETARY INTAKES AND HEALTH RISK ASSESSMENT - Alaa Eldin Morshdy; Mohamed Hussein; Wageh Darwish; Rawayeh Yousef; Ahmed Tharwat (Slovenian Veterinary Research, 2021)
Abstract: Canned fish is considered as an important fish product that can supply humans with part of their needs from essential amino acids, polyunsaturated fatty acids, vitamins, and minerals. However, canned fish might become a source of human exposure to xenobiotics such as heavy metals. This study aimed to estimate the residual contents of six heavy metals, namely lead (Pb), cadmium (Cd), arsenic (As), mercury (Hg), aluminum (Al), and tin (Sn) in four kinds of commercially purchased canned fish products from Zagazig city, Egypt. Eighty imported samples including canned anchovies, canned mackerel, canned sardine, and canned tuna (20 samples/each canned fish product) were examined. Besides, we calculated the estimated daily intakes (EDI), and potential health risks, hazard quotient (HQ), and hazard index (HI), of the examined heavy metals associated with the consumption of such fish products among Egyptian population. The obtained results revealed residual concentrations of the tested heavy metals higher than the established maximum permissible limits (MPL) by European Commission for Pb in 20%, 95%, and 100% of the examined canned anchovies, sardine, and tuna, respectively. Whereas, 80%, 100%, 100%, and 100% of the examined canned anchovies, mackerel, sardine, and tuna, respectively exceeded MPL of As. None of the examined samples exceeded MPL of Cd, Hg, Al, and Sn. The calculated HQ and HI for the examined heavy metals based on the daily intakes revealed values greater than 1.0 indicating potential human health risks. Therefore, it is highly advisable to reduce our daily intake of canned fish.